Analysis of The Influence of Managerial Skills and The Charisma of The School Principal in Improving Performance and Teacher Professionalism - Iwan Aprianto; Andri Astuti; Hairul Fauzi; Maisarah Gusvita; Iswanto Iswanto (JETL (Journal of Education, Teaching and Learning), 2023)
The objective of this study is to examine how the managerial skills and charisma of the school principal impact the performance and professionalism of teachers at MA A Yani Bangil and MA Al-Hikmah Bangil. The study adopts a quantitative research design with a cross-sectional approach. The participants in the research are teachers employed in both institutions, selected through purposive sampling. Data were collected using questionnaires that assess managerial skills, the school principal's charisma, teacher performance, and teacher professionalism. Data analysis involved descriptive statistics and multiple regression tests. The findings of the study demonstrate that both managerial skills and the school principal's charisma significantly influence teacher performance and professionalism. Specifically, the managerial skills of the school principal positively affect teacher performance and professionalism, and the school principal's charisma also has a positive impact on teacher performance and professionalism. These findings indicate that school principals with strong managerial skills and charismatic qualities can shape the performance and professionalism of teachers in the context of these educational institutions. This study contributes significantly to understanding the factors that influence teacher performance and professionalism. The implications of these findings emphasize the importance of focusing on the development of school principals' managerial skills and enhancing their charisma to enhance teacher performance and professionalism. Moreover, this research lays the groundwork for future studies exploring additional factors that may influence teacher performance and professionalism in different educational settings.